1998
DOI: 10.1111/j.1151-2916.1998.tb02304.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grain‐Boundary Phase on Dynamic Compression Fatigue in Hot‐Pressed Silicon Nitride

Abstract: Two types of hot-pressed silicon nitride, one having an amorphous grain-boundary phase (6 wt% yttria, 3 wt% alumina) and the other having a predominantly crystalline grain-boundary phase (8 wt% yttria, 1 wt% alumina), were tested on a split Hopkinson pressure bar with a momentum trap, such that, in each test, the sample was subjected to a single predefined stress pulse and then recovered without being subjected to any other loads. The specimens were loaded repeatedly with a triangular pulse of 3.2 GPa amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…So far, sintering of silicon nitride to high densities has demanded the addition of metal oxides [21,[143][144][145], nitrides as AlN [16,146,147] and rare earth oxides [143,[148][149][150]. According to Negita [21], an important condition for effective metal oxide sintering aids is that they do not decompose Si 3 N 4 to N 2 and SiO 2 or SiO gas in the sintering process, i.e.…”
Section: Pressureless Sinteringmentioning
confidence: 99%
“…So far, sintering of silicon nitride to high densities has demanded the addition of metal oxides [21,[143][144][145], nitrides as AlN [16,146,147] and rare earth oxides [143,[148][149][150]. According to Negita [21], an important condition for effective metal oxide sintering aids is that they do not decompose Si 3 N 4 to N 2 and SiO 2 or SiO gas in the sintering process, i.e.…”
Section: Pressureless Sinteringmentioning
confidence: 99%
“…Usually, pressureless sintering of nano‐sized ceramics particles into bulk dense bodies requires a specific green‐body microstructure that cannot be easily obtained . Pressure‐assisted sintering techniques (hot pressing, sinter forging, hot isostatic pressing, spark plasma sintering, etc.) provide an alternative approach to achieve ceramics with high density and fine grains.…”
Section: Introductionmentioning
confidence: 99%
“…Both uniaxial pressure and isostatic pressure have been extensively explored . While pressure‐assisted sintering of Si 3 N 4 has been practiced for a few decades, the current pressure‐assisted sintering methods are all conducted under constant pressure . In the previous study, we reported a novel vibration‐assisted hot‐pressing (VAHP) technique.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] While pressure-assisted sintering of Si 3 N 4 has been practiced for a few decades, the current pressure-assisted sintering methods are all conducted under constant pressure. 12 In the previous study, 13 we reported a novel vibration-assisted hot-pressing (VAHP) technique. Flexural strength of the VAHP prepared zirconia ceramic increased from 1224 MPa to 1556 MPa; also, the Y-TZP grains were confined in a narrow size range.…”
Section: Introductionmentioning
confidence: 99%